Liquidity: A New Monetarist Perspective - Lagos, Ricardo; Rocheteau, Guillaume; Wright, Randall (Journal of Economic Literature, 2017)
This essay surveys the new monetarist approach to liquidity. Work in this literature strives for empirical and policy relevance, plus rigorous foundations. Questions include: What is liquidity? Is money essential in achieving desirable outcomes? Which objects can or should serve in this capacity? When can asset prices differ from fundamentals? What are the functions of commitment and collateral in credit markets? How does money interact with credit and intermediation? What can and should monetary policy do? The research summarized emphasizes the micro structure of frictional transactions, and studies how institutions like monetary exchange, credit arrangements, or intermediation facilitate the exchange process. (JEL E24, E31, E42, E44, E52, G10, G21)